Direct RNA sequencing reveals m6A modifications on adenovirus RNA are necessary for efficient splicing - Alexander M. Price (Nature Portfolio, 2020)
Adenovirus transcripts contain N6-methyladenosine (m6A) modification. Here the authors profile m6A modification sites on adenovirus mRNAs using Illumina meRIP-Seq and nanopore direct RNA sequencing, and showcase a role for m6A in splicing of viral late mRNAs.